Ensaios enzimáticos com serino proteases: a) calicreína tecidual do rato; b) ß-tripsina bovina - Claudia Morais Vivas (2007)
-trypsin kinetic characterization using D-Val-Leu-Arg-Nansubstrate, in the absence and the presence of 4-nitroaniline inhibitor (4-NAn). The trypsin is a good experimental model for serino proteases characterization and the investigation of enzymatic inhibition is important to the establishment of enzyme action mechanism and to know about the specific interaction between the inhibitors and the enzymes, being possible the use of this knowledge in various diseases therapy. Thehydrolyses of D-Val-Leu-Arg-Nan substrate, catalyzed by the bovine -trypsin at pH 8,1 and 37ºC were carried out in a gradient of 4-NAn concentration. The results showed that the hydrolyses followed the Michaelis-Menten kinetics on the wide range of concentration substrate used. At low concentrations, the 4-NAn showed linear mixedinhibition, but at higher inhibitor concentrations, the parabolic inhibition was observed. The parabolic inhibition indicates the presence of a secondary binding site of the enzyme for the substrates besides its active center. The 4-NAn inhibits the enzyme binding with the same affinity to both its active center and the secondary site. Besides that, the inhibition of bovine -trypsin by 4-NAn is interesting data found since thiscompost is a hydrolyses product of anilide substrates.